Replantation of an Avulsed Maxillary Incisor after 12 Hours: Three-Year Follow-Up - Moradian, Hamid; Badakhsh, Samaneh; Rahimi, Mehran; Hekmatfar, Somayeh (Iranian Endodontic Journal, 2013)
Tooth avulsion is defined as the complete displacement of the tooth out of its alveolar socket. The treatment of choice is immediate replantation or if that is not possible, placement of the tooth in an appropriate storage media. This report presents replantation of an avulsed maxillary central incisor after 12 hours of storage in milk. The tooth was replanted and splinted. One week later, it was treated endodontically and calcium hydroxide dressing was placed for 1 month; subsequently, the tooth was obturated with gutta-percha. During three years of follow-up, no evidence of ankylosis or inflammatory resorption was observed. After three years, the tooth was stable and remained functional and esthetically acceptable.